ANALISIS PRODUKTIVITAS DAN OPTIMASI BIAYA OPERASIONAL ALAT BERAT PADA PEKERJAAN GALIAN PROYEK B-QUIK VETERAN, JAKARTA SELATAN - Ervina Yuliyanti Yuliyanti; Asri Winita; Al Faqih Azzhami Kusworo; Salsabila Wahyu Ramadhani; M. Abdul Aziz (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2026)
Mechanical earthmoving is a critical component in construction project execution that significantly affects time and cost efficiency. This study analyzes the productivity of a combined heavy equipment system consisting of a Komatsu PC78US excavator and a Mitsubishi Canter FE dump truck at the B-Quik Veteran Auto Workshop Construction Project in South Jakarta, with an excavation volume of 1,485.91 m³ and a hauling distance of 10 km. The existing condition, using one excavator and one dump truck, resulted in a productivity imbalance that extended project completion to 32 days, twice the initial 16-day target. By optimizing the equipment combination through the addition of one dump truck, total productivity increased from 18 m³/hour to 24.01 m³/hour. Results show that the project can be completed within 16 working days (128 hours) with a cost saving of IDR 24,005,120 compared to the existing condition. This study demonstrates that synchronization between excavation and hauling equipment is the key factor in heavy equipment management optimization.